Evaluation of Diagnostic Accuracy of Ultrasonography and Low Dose Computed Tomography in Acute Appendicitis - Saradiq Mudhafar Jebur; MahmoodRadhi Jobayr; Haider Abdulameer Ghayad (Indian Journal of Forensic Medicine & Toxicology, 2021)
In acute appendicitis, abdominal Ultrasonography (USG) to reach a stable diagnosis and use of Low DoseComputed Tomography (LDCT) in the diagnosis of acute appendicitis is crucial. This study aimed atassessing of the accuracy of imaging modalities (USG and LDCT) in the diagnosis of children and adultswith acute appendicitis to minimize the rate of negative appendectomyA total of 42 patients, children andadults were examined, were included in this research (16 females and 26 males) ages was ranged from 5 to45 years. All patients were examined byUSG and LDCT to diagnosis acute appendicitis . The sensitivityof low dose a LDCT scan was used to diagnose acute appendicitis (96.0%) that means LDCT was able todiagnosed (96.0%) Correctly diagnose acute appendicitis patients. The specificity of LDCT in the diagnosisof acute appendicitis was (50.0%) that mean LDCT was able to diagnosed half of those with diagnosis otherthan acute appendicitis correctly, But the sensitivity of USG in diagnosis of acute appendicitis was (54.1%)that mean ultrasound was able to diagnosed (54.1%) of patients diagnosed by CT scan as acute appendicitiscorrectly.The use of low-dose computerized tomography (LDCT) provides significantly higher diagnosticaccuracy compared to ultrasound for the detection of acute appendicitis.